Know Your Students and Where They Come From - Lobb, Richard (Australian and International Journal of Rural Education, 2020)
The entire Broome Senior High School community has worked over many years to ensure students are afforded a holistic, high-quality education which addresses and strengthens their individual academic and wellbeing needs. In particular, Broome Senior High School's strong approach to supporting its more than 300 Aboriginal students, who come to the school from all parts of the Kimberley and from across Australia, is one example of how to cater for the individual needs of a unique cohort of students.